Hydrogen storage capacities of alkali and alkaline-earth metal atoms on SiC monolayer: A first-principles study. (3rd June 2021) - Arellano, Lucía G.; de Santiago, Francisco; Miranda, Álvaro; Salazar, Fernando; Trejo, Alejandro; Pérez, Luis A.; Cruz-Irisson, Miguel
Abstract: A detailed theoretical Density-Functional-Theory-based investigation of hydrogen adsorption on silicon carbide monolayers (SiC-ML) decorated with alkali and alkaline-earth metal atoms is presented. The results show that the favourable position for all adsorbed metal atoms is above a Si atom. These metal atoms are chemisorbed to the SiC-ML, except for Mg which is physisorbed. The adsorbed atoms act in turn as adsorption sites for H2 molecules. The single-sided K-functionalized SiC-ML can store up to six H2 molecules. For double-side K-decorated SiC-ML, up to ten H2 molecules can be captured. In all cases, the H2 molecules are physisorbed. This is beneficial because the breaking of chemical bonds, which otherwise would be needed to make use of the stored H2, is energetically expensive. These results find decorated SiC-ML as a promising material for hydrogen storage systems. Graphical abstract: Image 1 Highlights: Alkali and alkaline-earth metal adatoms on SiC monolayers (SiC-ML) were studied. Li, Na, K and Ca decoration could improve the H-storage capacity of SiC-ML. The maximum capacity is six H2 for the K-decorated SiC-ML. Mg is not chemisorbed on the SiC-ML; thus, it cannot adsorb any H2 molecules. H2 molecules are always weakly physisorbed on all the decorated SiC-ML.